Perioperative Risk Factors Associated With Unplanned Reoperation Following Vascularized Free Flaps Reconstruction of the Oral Squamous Cell Carcinoma. Issue 8 (2nd November 2022) - Fu, Ganglan; Wang, Chengli; Zeng, Chengbo; Liu, Zhongqi; Han, Zhixiao; Huang, Haoquan; Cao, Minghui
Abstract : Objectives: To find out the occurrence rate and risk factors of unplanned reoperation (any unscheduled surgery within 30 d after the initial surgery) in patients who have received oral squamous cell carcinoma (OSCC) surgery and vascularized free flap reconstruction. Patients and Methods: We organized a retrospective study of 1058 patients who underwent OSCC resection and reconstruction with vascularized free flaps from 2011 to 2019. Clinical characteristics, reasons for unplanned reoperation, flap types, and previous treatment were compared between the unplanned reoperation group and the control group. Univariate and multivariate analyses were performed to identify perioperative risk factors for unplanned reoperation. The related perioperative factors that may influence perioperative infusion were included in propensity score matching to investigate the independent contribution of intraoperative colloid infusion on unplanned reoperation. Results: The overall rate of unplanned reoperation in OSCC patients was 11% (n=115). Flap necrosis and bleeding were the most common causes. Higher American Society of Anesthesiologists (ASA) grade [odds ratio (OR)=1.709, P =0.009], postoperative anemia (OR=0.983, P =0.011) and excessive intraoperative colloid input (OR=1.55, P =0.037) were identified as risk factors for unplanned reoperation. Propensity score matching was applied, and the difference of unplanned reoperation incidence between the matched groups was statistically significant (14.59% versus 8.54%; P =0.025). The multivariate analyses after propensity score matching confirmed that the intraoperative rate of colloid infusion of more than 2.3 mL/kg/h (OR=1.756, P =0.042) and prior radiotherapy (OR=2.78, P =0.001) are independent risk factors for unplanned reoperation. Conclusion: High intraoperative colloid infusion rate and prior radiotherapy may increase the risk of unplanned reoperation in patients who underwent OSCC surgery and vascularized free flap reconstruction.